Removal of Amitriptyline from Aqueous Media Using Activated Carbons - J.M. Valente Nabais; B. Ledesma; C. Laginhas (Adsorption Science & Technology)
This paper reports the removal of amitriptyline, a widely used tricyclic anti-depressant, from aqueous solutions by six activated carbons produced from cork, coffee endocarp and eucalyptus pulp. The results of this study showed that samples from cork and eucalyptus pulp, activated at 800 °C, exhibited the highest adsorption capacity of 120 mg/g and 110 mg/g, respectively. Samples produced from coffee endocarp showed the lowest capacity. Amitriptyline adsorption was almost independent of the pH of the solution and occurred via three different mechanisms based on the dispersive and chemical interactions between amitriptyline molecules and the carbon surface.